Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Ulang Konsumen Hand and Body Lotion Marina di Kota Bandung - Salsabila Putri Septi; Edi Nurtjahjadi (Penerbit Goodwood, 2023)
Purpose: This study aims to analyze the effect of product quality and price on consumer repurchase intention of Marina hand and body lotion in Bandung City. Research methodology: This study used a quantitative approach with an online questionnaire survey method. Data analysis included multiple regression using SPSS version 25. Results: The results showed that product quality and price partially had a positive and significant effect on repurchase intention. Limitations: This study used 100 respondents who had used Marina's hand and body lotion products with a limited research focus only in the city of Bandung. Contribution: The findings of this study can contribute to further research and can be used as a basis for consideration in Marina company decision making to keep consumers buying back products by increasing product quality and price. Novelty: Testing the effect of product quality and price on repurchase intention in research subjects who had used Marina's hand and body lotion products, with the majority of student respondents living in Bandung as the locus of research.